First record of the genus Scelio (Hymenoptera: Platygastridae, Scelionidae, Scelioninae) egg parasitoids in tomato greenhouses of southeastern Algeria - Wahiba, Afissa; Fatma, Demnati; Faiza, Marniche; Nacima, Deghiche-Diab (ENTOMOLOGIA HELLENICA, 2022)
This is the first record of genus Scelio (Latreille, 1805) in Algeria. Two species of Scelio poecilopterus (Priesner, 1951) and Scelio vulgaris (Kieffer, 1908), were collected in tomato greenhouses from El Alia and El Hadjeb regions in the province of Biskra, southeastern Algeria in 2019-2020, using yellow pan traps, yellow bottles and Barber traps for sampling specimens, followed by laboratory methods to preserve and identify the samples. Photographic material and information on these species are presented and described, on female specimens, in order to expand the knowledge about the distribution and biodiversity of egg parasitoids in our country.